Accountability for the Distribution of Social Assistance for the Family Hope Program in an Effort to Improve Community Welfare (Case Study in the Mandailing Natal District Social Service Office - Juriah Juriah; ); Nur Fadhilah Ahmad Hasibuan (Penerbit Jurnal Indonesia, 2022)
In this study,the researchers focused on the Family Hope Program (PKH),especially in the Social service office of Mandailing Natal regency,which is one of the policies to overcome poverty. In 2019, 2020, 2021 and 2022 the poverty rate in Mandailing Natal regency is not static but fluctuating according to changes in components and can change because there is such a thing as natural graduating and independent graduation, but in 2021 the poverty rate has decreased,namely from 19.409 to 17,107 in 2022. The disbursement of PKH assistance funds is carried out 4 (four) times in a year. The amount received by KPM per year varies according to the KPM component to can change at each stage starting from Rp. 900.000 – Rp. 9.200.000 per year or if there are Rp. 225.000, Rp. 375.000 and Rp. 600.000 umtil there is Rp. 2.300.000 per stage or per three years. The purpose of this study was to determine the distribution of social assistance for the family of hope program in Dinas Social Mandailing Natal regency and to analyze the inhibiting factors for its implementation and the efforts made to overcome these inhibiting factors. The method used is descriptive research With technical qualitative descriptive analysis. The object of this research is to analizyze the accountability of the distribution poof PKH at the DINSOS of Mandailing Natal regency, the subject of thisresearch is KORKAB PKH. This research was counducted at the Social service of Mandailing Natalregency. The type of data used by researchers in this study is primary data. With data sources in the from of books,literature,documentztion results,observations (observations) by looking at PKH records from 2019 to 2022,and direct interview with Mr. Aswan Lubis as KORKAB PKH at the social service of Mandailing Natal regency. The results showed that the Accountability for the distribution of social assistance for the Family Hope Program (PKH) in Dinas Social Mandailing Natal regency had not been effective. Based on the research conducted, it can be councluded that the distribution of social assistance for the Family Hope Program (PKH) in Dinas Sosial Mandailing Natal regency has not been effective and improvements are still needed in several indicators such as the accuracy of targeting beneficiaries according to the criteria for recipients of assistance,timeliness of assistance to the recipients, skills of recipients assistance to use the e-PKH application